Religious Moderation in Sayyid Qutb’s Fī Ẓilāl al-Qur’ān: A Thematic Reconstruction of Qur’anic Interpretation - Syaiful Arief (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD, 2025)
This article examines the concept of religious moderation in Sayyid Qutb’s Fī Ẓilāl al-Qur’ān, a Qur’anic commentary often associated with radical Islamist ideology. Challenging this dominant perception, the study aims to reconstruct Qutb’s moderate interpretations through a thematic analysis of Qur’anic verses addressing tolerance, da‘wah ethics, interreligious relations, and Muslim brotherhood. Employing qualitative library research and content analysis, this study situates Qutb’s interpretations within their textual and socio-political contexts. The findings demonstrate that, despite his strong ideological critique of modern society, Qutb consistently articulates moderation at the ethical and social level. The interpretation rejects coercion in religion, promotes wisdom and gentleness in da‘wah, and emphasizes justice and benevolence toward non-Muslims who do not engage in hostility. However, the study also reveals an internal tension between these ethical principles and Qutb’s broader political vision. This research contributes to Qur’anic studies by offering a more balanced and nuanced understanding of Sayyid Qutb’s exegetical legacy.